Generation Z At the Workplace: Leadership and Management Style (A Review of Related Literatures) - M. Ilagan, Gene Kenneth; Hudtohan, Emiliano T. (International Journal of Management and Education in Human Development, 2024)
Generation Z poses both a threat and an opportunity for any organization’s management. Generation Z are those born between the mid-199s and early 2010s and are known to have a distinctive professional approach, traits, and work habits that are shaped by technology. To effectively manage this new generation of employees, this study collated various research that determine the identity of Gen Z in terms of work ethics, professionalism, management, and leadership approach. Through this analysis of multiple research outputs, this paper aims to provide different understandings and approaches one may use to manage the new generation of professionals well. In addition, this will be used as a review of related literature in a study that will be conducted in the Philippines, particularly in industries known to have more Gen Z employees: Technology and BPO industries. The goal is to provide an evidence-based recommendation to increase the productivity, retention, and efficiency of the new generation.